2011
DOI: 10.1080/19439342.2010.549947
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water supply and sanitation assistance on human welfare in rural Pakistan

Abstract: The paper examines impact of two water supply and sanitation projects in rural Pakistan in improving access to water supply and sanitation and on health, education, and labour supply based on a household survey of 1300 project and 1300 comparison households. The impact was estimated using treatment effects based on a control-function approach. Overall findings show that the projects improved households' access to water supply, reduced drudgery associated with fetching water and improved attendance of high-scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“…Although their study was limited by a small sample size, their findings are supported by the studies including qualitative data derived from people who collect water. They are also supported by the findings of Rauniyar et al , 29 who attributed a significant 5% reduction in the ‘drudgery’ of water fetching among the lowest socioeconomic group to water supply projects, and the findings of Porter et al , 60 who found high proportions of children reporting pain as a direct result of load-carrying, which particularly for girls, included water carriage by head loading. However, as highlighted by Porter et al , 60 61 individuals in low-income and middle-income countries carry diverse loads, and water may not be the heaviest load carried.…”
Section: Resultsmentioning
confidence: 54%
“…Although their study was limited by a small sample size, their findings are supported by the studies including qualitative data derived from people who collect water. They are also supported by the findings of Rauniyar et al , 29 who attributed a significant 5% reduction in the ‘drudgery’ of water fetching among the lowest socioeconomic group to water supply projects, and the findings of Porter et al , 60 who found high proportions of children reporting pain as a direct result of load-carrying, which particularly for girls, included water carriage by head loading. However, as highlighted by Porter et al , 60 61 individuals in low-income and middle-income countries carry diverse loads, and water may not be the heaviest load carried.…”
Section: Resultsmentioning
confidence: 54%
“…In a seminal work, Rosenbaum and Rubin (1983) proposed PSM as a method to reduce the bias in the estimation of treatment effects with observed data sets. Matching methods have become increasingly popular and widely used in the evaluation of development interventions (Becker & Ichino, 2002;Ravallion, 2008;Rauniyar, Orbeta, Jr., & Sugiyarto, 2010;Kumar & Vollmer, 2013).…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…Following other studies that used observational data to draw out the causal impact of water supply and sanitation facilities on child health, 17,18 we estimate the average treatment effect on the treated (ATT) using propensity score matching. 19 We apply this method on a data set comprising all rural households with children younger than 5 years from the 1993, 1998, 2003, and 2008 rounds of the National Demographic and Health Survey (NDHS) 20 undertaken by the Philippine National Statistics Office.…”
Section: Methodsmentioning
confidence: 99%